The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.4196/kjpp.2014.18.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Asarone, a Major Component ofAcorus gramineus, Attenuates Corticosterone-Induced Anxiety-Like Behaviours via Modulating TrkB Signaling Process

Abstract: We investigated the anxiolytic-like activity of α-asarone (AAS) from Acorus gramineus in an experimental rat model of anxiety induced by repeated administration of the exogenous stress hormone corticosterone (CORT). The putative anxiolytic effect of AAS was studied in behavioral tests of anxiety, such as the elevated plus maze (EPM) test and the hole-board test (HBT) in rats. For 21 consecutive days, male rats received 50, 100, or 200 mg/kg AAS (i.p.) 30 min prior to a daily injection of CORT. Dysregulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Pharmacological studies have proved that aasarone has effect on central nervous inhibitory, and was applied in epilepsy, asthma, and depression treatment (Lee et al 2014;Lu et al 2014;Huang et al 2013;Su et al 2014). However, the neuroprotective effects of b-asarone were highly suggested in recent studies, especially in AD investigation (Zou et al 2011;Liu et al 2010;Geng et al 2010;Wei et al 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Pharmacological studies have proved that aasarone has effect on central nervous inhibitory, and was applied in epilepsy, asthma, and depression treatment (Lee et al 2014;Lu et al 2014;Huang et al 2013;Su et al 2014). However, the neuroprotective effects of b-asarone were highly suggested in recent studies, especially in AD investigation (Zou et al 2011;Liu et al 2010;Geng et al 2010;Wei et al 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Anxiety-like behaviors observed in rats that underwent hypoxia-ischemia [ 69 , 70 ] were prevented by resveratrol. Head-dipping behavior in the HBT is considered to be a good index for evaluating the anxiety of rodents [ 71 ]. Impairments in reference and working memory evaluated in the T-maze performance were demonstrated after neonatal hypoxia-ischemia, as previously reported [, 68 , 72 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that restraint stress-submitted groups were more anxious than nontreated groups [ 35 37 ] and increment of corticosterone had an anxiolytic-like effect in animal model [ 38 ]. Central and peripheral IL-4 concentration had an effect of suppressing LPS-induced sickness behavior [ 39 , 40 ] and IL-4 −/− mice exhibited more anxious behavior compared to wild type [ 41 ].…”
Section: Discussionmentioning
confidence: 99%